Evaluasi dan Perancangan Ulang UI/UX Website Dealer Otomotif Menggunakan Design Thinking dan User Experience Questionnaire - Octarian Rudy Husin; Ahmad Farisi (Arcitech: Journal of Computer Science and Artificial Intelligence, 2026)
The rapid growth of digital transformation has encouraged automotive dealer websites to function not only as information platforms but also as tools that provide effective and engaging user experiences. However, previous UI/UX studies have primarily focused on education, e-commerce, and general service sectors, while research on automotive dealer websites remains limited. This study aims to redesign the user interface and user experience of the Dealer ABC Palembang website using the Design Thinking method and evaluate its user experience quality through the User Experience Questionnaire Short Version (UEQ-S) and the User Experience Questionnaire (UEQ). The research was conducted through the five stages of Design Thinking: empathize, define, ideate, prototype, and testing. The initial evaluation using UEQ-S involved 42 respondents, while the final evaluation using UEQ involved 38 respondents after prototype testing. The results indicate positive scores across all UEQ dimensions, namely Attractiveness (1.33), Perspicuity (2.02), Efficiency (2.06), Dependability (1.93), Stimulation (1.97), and Novelty (1.49). Based on the UEQ benchmark, Perspicuity and Efficiency achieved the Excellent category, while the remaining dimensions were classified as Above Average to Good. These findings demonstrate that Design Thinking effectively enhances the user experience quality of automotive dealer websites.